IS THERE A RELATIONSHIP BETWEEN FINANCIAL LITERACY, CAPITAL STRUCTURE AND COMPETITIVENESS OF SMEs? (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The importance of financial market development for the economic development and competitiveness of a country is reflected in channelling of capital towards those investments that have the highest returns, thus ensuring liquidity and efficient grouping of enterprises, that is, risk-taking. Efficient risk-taking is primarily reflected in the availability of a large number of sources of funding, which allow enterprises freedom when forming their capital structure. Enterprises that do not have a large number of sources of funding at their disposal have to resort to debt financing when forming their capital structure, which ultimately means excessive financial vulnerability. Financial vulnerability, especially in times of the financial crisis, when fluctuations in the cost of capital are very high, reduces investment, growth and employment in the long-term. Small and medium-sized enterprises in the Croatian underdeveloped financial market must resort to borrowing, as the most readily available source of funding. Analysing the process of decision-making about capital structure on a sample of 108 small and medium-sized enterprises, it was observed that enterprises whose capital structure is less dependent on debt achieve better financial results and growth. The process of making financial decisions in those companies is in the hands of owners and/or managers and consultants with knowledge about the advantages and disadvantages of individual sources of funding. Financial knowledge is one of the most important determinants of the capital structure that will enable the growth and development of the small and medium-sized enterprise sector, as well as greater competitiveness of enterprises, regardless of size, activity, industry and the form of ownership of these enterprises.T-test and Levene’s test of equality of variances were used to investigate the relationship between the profitability of enterprises and their financial literacy.Keywords: Financial knowledge, capital structure, small and medium-sized enterprises, financial market, competitiveness